Incorporating sub-universes to address the issue of Chagas in different educational contexts - Sanmartino, Mariana (2013)
Although Chagas has been traditionally addressed just from a biomedical point of view, due to its multiple factors and the diverse actors involved, it is necessary to consider it as a really complex problem characterized by four large dimensions: biomedical, epidemiological, sociocultural, and politico-economic. A comprehensive analysis of the problem is thus needed, in order to obtain effective and long-term solutions, appropriate to the different contexts where Chagas exist. In this text we share our ideas and experiences that we have applied to activities, didactic materials and resources that aim at creating a comprehensive view of this environmental and health issue, by providing elements and actors that are usually disregarded. Art, science and popular knowledge get dynamically combined in a group of proposals developed to provide all of us with the opportunity to observe and feel beyond dichotomies and traditional approaches.